Impact of previous insulin therapy on the prognosis of diabetic patients with acute coronary syndromes - António,Natália (2010)
OBJECTIVE: To determine whether previous insulin treatment independently influences subsequent outcomes in diabetic patients with ACS (acute coronary syndromes). SUBJECTS AND METHODS: 375 diabetic patients with ACS, divided in 2 groups: Group A (n = 69) - previous insulin and Group B (n = 306) - without previous insulin. Predictors of 1-year mortality and major adverse cardiac events (MACE) were analyzed by Cox regression analysis. RESULTS: Group A had more previous stroke (17.4% vs. 9.2%, p = 0.047) and peripheral artery disease (13.0% vs. 3.6%, p = 0.005). They had significantly higher admission glycemia and lower LDL cholesterol. There were no significant differences in the type of ACS, in 1-year mortality (18.2% vs. 10.4%, p = 0.103) or MACE (32.1% vs. 23.0%, p = 0.146) between groups. In multivariate analysis, insulin treatment was neither an independent predictor of 1-year mortality nor of MACE. CONCLUSION: Despite the more advanced atherosclerotic disease, diabetics under insulin had similar outcomes to those without insulin. Insulin may protect diabetics from the expected poor adverse outcome of an advanced atherosclerotic disease.